Eltroplectris paranaënsis: a new species of Spiranthinae (Orchidaceae) from the nebular Atlantic Rain Forest - Engels, Mathias Erich; Silva-Pereira, Viviane Da; Smidt, Eric De Camargo (Phytotaxa, 2023)
During a field expedition to the Serra do Mar in the state of Paraná, a new species of Spiranthinae was found, which occurs as a humicolous in the understory of the Upper Montane Dense Ombrophilous Forest, also called Cloud Forest. Phylogenetic analysis of the Stenorrhynchos clade, in which the genus is inserted, using nuclear internal transcriber spacer data, confirms that the new species belongs to the genus Eltroplectris with high support, and it is a sister to the species E. triloba and E. schlechteriana. Eltroplectris paranaënsis can be recognized and differentiated from congeners by its small habit, leaves with a narrow-elliptical-lanceolate blade, parviflorous inflorescence, light-green and white flowers, and the trilobed lip with an entire margin.